DEPRECIATION AND PUBLIC UTILITY VALUATION. - Bauer, John (The Accounting Review, 1930)
Abstract The object of depreciation accounting and the object of accounting generally, is to show costs. With this view, the accounts would supply the financial records of a business. Materials which are purchased and used in a particular accounting period, go entirely with their full cost into the operating account for that period. A machine with a life of ten years is purchased no less for operating purposes, and ultimately must be included entirely in the operating costs. If the purpose of accounting is to show costs, then the original cost of the machine must be charged originally to capital account and then distributed or allocated by periods to show the cost of operation for each period of the ten years. The object of public utility regulation is largely rate control. The significance of the accounting, including all provisions for depreciation, depends upon ratemaking policies, how and upon what basis rates are made. The common conception, however, is that rates shall be based on costs. Reasonable rates are rates that cover the cost of service. The rates in the aggregate provide for the aggregate costs. This applies to operating expenses, to maintenance, taxes and to all the ordinary operating items.